The effect of the pandemic on restaurants and social marketing strategies for it - Karabağlı, Eren (İstanbul Bilgi Üniversitesi, 2022)
ABSTRACT: The coronavirus disease, which first appeared in Wuhan, China at the end of 2019, turned into an epidemic with its spread to other countries. With the increase in the number of cases, many countries have tried to keep the epidemic under control by taking various measures. Along with the pandemic, the concept of digitalization has gained a special importance. People have started to do most of the things they used to do digitally due to the pandemic. With the onset of the pandemic, people who had to live a different life from their old lives are trying to get used to this situation. This situation, which is called the new normal, also applies to businesses. The changing life due to the pandemic has brought with it the necessity of change in all areas. During and after the pandemic, many things are and will be different from before the pandemic. In this direction, businesses also need to make changes at many points due to the pandemic, considering their own situation and future. Covid19 has had an impact on all industries. Within the scope of this thesis, the focus is on the restaurant sector, and how they are affected by the pandemic and what social marketing strategies they apply are investigated. First of all, the intricacies of social marketing were defined, and suggestions were compiled on how to deal with this crisis worldwide and what more could be done. According to research, many businesses have accelerated their digitalization steps and social responsibility efforts with the onset of the pandemic. It is seen that businesses that digitalize and implement social marketing strategies, especially in an environment where marketing activities are significantly affected, gain competitive advantage.

ÖZET: İlk olarak 2019 yılının sonunda Çin’in Wuhan şehrinde ortaya çıkan koronavirüs hastalığı diğer ülkelere yayılmasıyla birlikte bir salgına dönüşmüştür. Vaka sayılarındaki artışla birlikte birçok ülke çeşitli önlemler alarak salgını kontrol altında tutmaya çalışmışlardır. Pandemi ile birlikte dijitalleşme kavramı da ayrı bir önem kazanmıştır. İnsanlar daha önce yaptıkları şeylerin büyük çoğunluğunu pandemi sebebiyle dijital olarak gerçekleştirmeye başlamışlardır. Pandeminin başlamasıyla birlikte eski hayatlarından farklı bir hayat yaşamak zorunda kalan insanlar bu duruma alışmaya çalışmaktadırlar. Yeni normal olarak adlandırılan bu durum işletmeler için de geçerlidir. Pandemi sebebiyle değişen hayat beraberinde tüm alanlarda değişim zorunluluğunu getirmiştir. Pandemi dönemi ve sonrasında birçok şey pandemi öncesinden farklı olmaktadır ve olacaktır. Bu doğrultuda işletmeler de kendi durumlarını ve geleceklerini düşünerek pandemi sebebiyle birçok noktada değişiklik yapma gereği duymaktadırlar. Covid-19 bütün sektörler üzerinde etki yapmıştır. Bu tez kapsamında restoran sektörüne odaklanılmış olup, pandemiden nasıl etkilendikleri ve ne gibi sosyal pazarlama stratejileri uyguladıkları araştırılmıştır. Öncelikli olarak sosyal pazarlamanın incelikleri tanımlanarak, dünya genelinde bu krizle nasıl başa çıkıldığına ve daha nelerin yapılabileceğine dair öneriler derlenmiştir. Araştırmalara göre birçok işletme pandeminin başlamasıyla birlikte dijitalleşme adımlarını ve sosyal sorumluluk çalışmalarını hızlandırmıştır. Özellikle pazarlama faaliyetlerinin önemli düzeyde etkilendiği bir ortamda dijitalleşen ve sosyal pazarlama stratejileri uygulayan işletmelerin rekabette avantaj elde ettikleri görülmektedir.